Promoting the Durdona Mungbean Variety in Karakalpakstan - Akramkhanov, Akmal (International Center for Agricultural Research in the Dry Areas, 2025)
This video highlights the promotion and cultivation of the Durdona mungbean variety under the local conditions of Karakalpakstan. Since 2021, seeds of this variety have been distributed to farmers across several provinces as part of a broader initiative. The work was carried out within the GIZ-led project "Ecologically Oriented Regional Development in the Aral Sea Region", with implementation support from ICARDA. This video, shot in 2024 during the final stages of the project, provides an overview of the variety's performance, seed production practices, and its potential for local farming systems.